2021
DOI: 10.3390/life12010043
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Systemic Inflammation Is Associated with Reduced Corticolimbic White Matter Integrity in Depression

Abstract: (1) Background: Growing evidence indicates that inflammation can induce neural circuit dysfunction and plays a vital role in the pathogenesis of major depressive disorder (MDD). Nevertheless, whether inflammation affects the integrity of white matter pathways is only beginning to be explored. (2) Methods: We computed quantitative anisotropy (QA) from diffusion magnetic resonance imaging as an index of white matter integrity and regressed QA on C-reactive protein (CRP), controlling for age, sex, and BMI, in 176… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 93 publications
0
4
1
1
Order By: Relevance
“…This literature shows that peripheral inflammation and changes in WM microstructure are associated with depression 28 , 34 , 38 . It would be interesting to see this in drug-naïve first-episode depression and in people in outpatient treatment to define endophenotypes in depression 40 .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…This literature shows that peripheral inflammation and changes in WM microstructure are associated with depression 28 , 34 , 38 . It would be interesting to see this in drug-naïve first-episode depression and in people in outpatient treatment to define endophenotypes in depression 40 .…”
Section: Introductionmentioning
confidence: 97%
“…Post-mortem and animal studies have demonstrated that peripheral inflammation is associated with WM injury 26 , 27 . Moreover, other experimental studies have also shown that psychological stress could cause the downregulation of the claudin-5, promoting the entrance of peripheral pro-inflammatory cytokines into the central nervous system and damaging the white matter integrity 28 30 . In addition, many studies have highlighted in the past decade the in vivo relationship between depression and peripheral inflammation 31 35 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, our previous study showed correlations between reduced integrity of the corpus callosum and increased levels of IFN-γ in SCH and IL-6 in HC [ 33 ]. Recently, Thomas et al [ 34 ] showed that systemic inflammation is associated with reduced white matter integrity of the CB in patients with depression. Correlations between the integrity of various brain regions, including the CB, and levels of peripheral inflammatory cytokines were also observed in patients with bipolar disorder [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…É possível que a falha no mecanismo de recuperação da resposta inflamatória possa ser responsável pela manutenção das queixas cognitivas em algumas mulheres, dada a variabilidade da resposta inflamatória entre os indivíduos -esta inclusive é a nossa crença. Recentemente, pesquisadores associaram altos índices de inflamação periférica com queda em índices de difusividade no cérebro de pacientes com depressão maior em áreas cortico-limbicas, (161) corroborando com o relatado aumento de sintomas depressivos durante inflamação. (162) Este também é um mecanismo biológico explorado para entender o quadro de fadiga relacionada ao câncer, (40) com a ação inflamatória por via do eixo hipotálamo-adrenal, ou por sua influência no sistema imune.…”
Section: Dados De Tensores De Difusãounclassified